Child and Adolescent Patients attending Psychiatric Out-Patient Department - Poudel, R; Shah, S; Gupta, U (Journal of Psychiatrists' Association of Nepal, 2018)
Introduction: Children and adolescent form significant group of patients in psychiatry. The aim of this study was to identify the prevalence and pattern of different disorders in children and adolescent attending psychiatry OPD.Material And Method: Socio-economic and other data of subjects 19 year and younger visiting the Out Patient Department (OPD) of Department of Psychiatry, Universal College of Medical Sciences (UCMS), Bhairahawa, Nepal was collected from the OPD register retrospectively. The duration of the study was one year, from January 2016 to December 2016. Diagnosis was made using the ICD 10. Data was analyzed using Statistical Package for the Social Sciences (SPSS) version 21.0 for Windows.Results: The total number of subjects enrolled for the study was 591. The mean age of the subject was 14.8 years (SD=2.8). Male constituted 44.67% (n= 264) of the subjects while female 55.33% (n=327). Majority of the subjects were from rural background (66%). The most common diagnosis was epilepsy (17.3%) followed by dissociative disorder (14.6%) and primary headache (11.8%) respectively. There was no statistically significant association of these major three disorders with age of the patient. Dissociative disorder was observed in 68 females compared to 18 males which was statistically significant (p=0.001).Conclusion: Children and adolescent visiting the psychiatry OPD are diagnosed with a variety of disorders. Psychiatrists’ Association of Nepal Vol. 6, No. 2, 201, Page: 36-41